Desenvolvimento (in) sustentável das indústrias cerâmicas da microrregião do Vale-do-Açu/RN - Cunha Neto, Francisco Assis da (2013)
A great discussion of this work refers to development that is related to the common census of economic growth, in addition, another component of this discussion is related to socio-cultural and environmental impacts of this conception of progress. Giving economic progress is not necessary, since the development in its fullness, that progress depends, but what is sought is a harmony between capital accumulation and environmental limits and social interactions between men and between them and nature. The presence or absence of this harmonious relationship can be observed in various industrial activities, more punctual can cite the example of the developed ceramic activity in the meso-Valley-Acu in Rio Grande do Norte where such activity has great economic representativeness for the region, but that does not have good relations with social and environmental issues and is more focused on the accumulation of capital by increasing its level of industrial activity. Given this debate, the present paper aims to present the profile of a ceramic tile Valley-of-Acu and impacts, ecosocioambientais generated as a result of this activity as well. Methodologically the research will be conducted through literature research papers in books and other work carried out on the same theme, the second time will be held the empirical part of the research through interviews with managers of industries (selected through sample with the criteria set later ) as well as with employees working on the factory floor and city managers in the region under analysis and other agencies responsible for regulation and control of activity potter in the state